An Exploratory Study of Police Officers’ Perceptions of Health Risk, Work Stress, and Psychological Distress During the COVID-19 Outbreak in China - Huang, Qiufeng; Bodla, Ali Ahmad; Chen, Chiyin (Frontiers in Psychology, 2021)
Objectives How do the police officers perceive health risk, psychological distress, and work stress during the COVID-19 outbreak in China? This study explores the health risk perception, work stress, and psychological distress of police officers who worked at the front-line to implement lockdown measures. Material and Methods We conducted a large-scale field survey (N=5,611) with police officers sample in the northwestern part of China from February 29 to March 7, 2020. Independent-sample T-test and ANOVA were used to analyze whether there are differences in health risk perception, work stress, and psychological distress between different groups. The regression analysis was employed to figure out the factors that influence police officers’ psychological distress. Results Results showed a gender difference in perceiving work stress among police officers. Also, police officers with chronic disease perceived higher health risks, more psychological distress, and higher work stress. Additionally, police officers above 45 years old significantly perceived higher health risks than young officers did. It also revealed that working hours contribute to police officers’ health risk perception, psychological distress, and work stress. Finally, our results highlight that age, working hours, chronic disease, health risk perception, and work stress significantly contribute to police officers’ psychological distress. Conclusions Our research verifies that there is a gender difference in perceiving work stress among police officers. Police officers with ongoing medical issues and above 45 years old suffer more during the COVID-19 outbreak in China. Our research suggests that the government should pay more attention to their physical health and mental health. The heavy workload containing the COVID-19 extends police officers’ working hours, causing higher health risks, work stress, and psychological distress. This study contributes to the psychological distress literature and provides a way forward to other countries struggling to contain the COVID-19.